Thermal creep transition stresses and strain rates in a circular disc with shaft having variable density. Issue 3 (3rd May 2016) - Thakur, Pankaj; Kaur, Jatinder; Bir Singh, Satya
Abstract : Purpose: – The purpose of this paper is to present study of thermal creep stresses and strain rates in a circular disc with shaft having variable density by using Seth's transition theory. Design/methodology/approach: – Seth's transition theory is applied to the problem of thermal creep transition stresses and strain rates in a thin rotating disc with shaft having variable density by finite deformation. Neither the yield criterion nor the associated flow rule is assumed here. The results obtained here are applicable to compressible materials. If the additional condition of incompressibility is imposed, then the expression for stresses corresponds to those arising from Tresca yield condition. Findings: – Thermal effect increased value of radial stress at the internal surface of the rotating disc made of incompressible material as compared to tangential stress and this value of radial stress further much increases with the increase in angular speed as compared to without thermal effect. Strain rates have maximum values at the internal surface for compressible material. Originality/value: – The model proposed in this paper is used in mechanical and electronic devices. They have extensive practical engineering application such as in steam and gas turbines, turbo generators, flywheel of internal combustion engines, turbojet engines, reciprocating engines, centrifugal compressors and brake discs.